Long non-coding RNA LOC284454 promotes migration and invasion of nasopharyngeal carcinoma via modulating the Rho/Rac signaling pathway. (30th October 2018) - Fan, Chunmei; Tang, Yanyan; Wang, Jinpeng; Wang, Yian; Xiong, Fang; Zhang, Shanshan; Li, Xiayu; Xiang, Bo; Wu, Xu; Guo, Can; Ma, Jian; Zhou, Ming; et al.
Abstract: Nasopharyngeal carcinoma (NPC) is a unique malignant cancer with high metastasis. Because the early symptoms of NPC patients are not obvious, most patients have distant metastases when diagnosed, which makes treatment difficult. Long non-coding RNAs (lncRNAs) are emerging as important regulators in human carcinogenesis. LncRNAs have been increasingly identified but remain largely unknown in NPC. Therefore, we performed gene expression profiling to screen for altered expression of lncRNAs in NPC tissues and adjacent samples. One lncRNA, LOC284454, was upregulated and associated with poor prognosis in NPC. In in vivo and in vitro assays, LOC284454 promoted the migration and invasion capacity of NPC cells. Mass spectrometry combined with bioinformatics suggested that LOC284454 affected the cytoskeletal and adhesion-related Rho/Rac signaling pathways. LOC284454 may be a potential novel treatment target and is expected to be a new diagnostic and prognostic marker in patients with NPC. Abstract : LncRNAs are emerging as important regulators in human carcinogenesis. We found that a novel lncRNA, LOC284454, was upregulated in nasopharyngeal carcinoma biopsies, and associated with poor prognosis. Further study suggested that LOC284454 affected cytoskeletal and adhesive related Rho/Rac signaling pathways.